The mentor leader - Dungy, Tony.; Whitaker, Nathan (Carol Stream, Ill. : Tyndale House Publishers, 2010)
"In 'The Mentor Leader', Tony Dungy shares the secrets of mentor leadership and why it's a vital part of developing a consistently winning team, Drawing on all-new stories and principles from his life and career, 'The Mentor leader' makes a case for the importance and effectiveness of mentor leadership; offers insight into some of Dungy's mentoring relationships; reveals the single most important thing that sets a mentor leader apart; and helps you discover the ultimate secret to building a winning team" --Cover, p. 2.
A different way to lead -- The mind-set of a mentor leader -- The maturity of a mentor leader -- The marks of a mentor leader -- The mandate of a mentor leader -- The model of a mentor leader : living the message -- The means of a mentor leader : maximizing team performance -- The methods of a mentor leader : the seven E's of maximizing potential -- The measure of a mentor leader : a life of significance -- Q&A with Tony Dungy.
Keywords: Leadership -- Religious aspects -- Christianity; Mentoring -- Religious aspects -- Christianity; Leadership; Mentoring